A distinct mitochondrial myopathy, lactic acidosis and sideroblastic anemia (MLASA) phenotype associates with YARS2 mutations. Issue 9 (5th August 2013) - Shahni, Rojeen; Wedatilake, Yehani; Cleary, Maureen A.; Lindley, Keith J.; Sibson, Keith R.; Rahman, Shamima
ABSTRACT: Nuclear‐encoded disorders of mitochondrial translation are clinically and genetically heterogeneous. Genetic causes include defects of mitochondrial aminoacyl‐tRNA synthetases, and factors required for initiation, elongation and termination of protein synthesis as well as ribosome recycling. We report on a new case of myopathy, lactic acidosis and sideroblastic anemia (MLASA) syndrome caused by defective mitochondrial tyrosyl aminoacylation. The patient presented at 1 year with anemia initially attributed to iron deficiency. Bone marrow aspirate at 5 years revealed ringed sideroblasts but transfusion dependency did not occur until 11 years. Other clinical features included lactic acidosis, poor weight gain, hypertrophic cardiomyopathy and severe myopathy leading to respiratory failure necessitating ventilatory support. Long‐range PCR excluded mitochondrial DNA rearrangements. Clinical diagnosis of MLASA prompted direct sequence analysis of the YARS2 gene encoding the mitochondrial tyrosyl‐tRNA synthetase, which revealed homozygosity for a known pathogenic mutation, c.156C>G;p.F52L. Comparison with four previously reported cases demonstrated remarkable clinical homogeneity. First line investigation of MLASA should include direct sequence analysis of YARS2 and PUS1 (encoding a tRNA modification factor) rather than muscle biopsy. Early genetic diagnosis is essential for counseling and to facilitate appropriate supportive therapy. Reasons for segregation of specific clinical phenotypes with particular mitochondrial aminoacyl tRNA‐synthetase defects remain unknown. © 2013 Wiley Periodicals, Inc.